(3CSFdI hCLhHI aj Gdabg Ydi WQjbI Ndjds
(3ChdgG (B:s
(3GdMeO ddg GdPj CfYe YdjfG HfYeI GdEjeGf hGdESdGe hLYdfG ef CeI fHjfG eMeO Ydjg CaVd GdUdGI hCRci GdSdGe s
(3BNQgG (B:s
(3GfJgi hGddg JYGdi CYde s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B- (3GdQHGW (B(D 207) s
Keywords: (3Gdabg GdeGdcjs